The Content and Size of Hyaluronan in Biological Fluids and Tissues - Cowman, Mary K.; Lee, Hong-Gee; Schwertfeger, Kathryn L.; McCarthy, James B.; Turley, Eva A. (Frontiers in Immunology, 2015)
Hyaluronan is a simple repeating disaccharide polymer, synthesized at the cell surface by integral membrane synthases. The repeating sequence is perfectly homogeneous, and is the same in all vertebrate tissues and fluids. The polymer molecular mass is more variable. Most commonly, hyaluronan is synthesized as a high molecular mass polymer, with an average molecular mass of approximately 1000-8000 kDa. There are a number of studies showing increased hyaluronan content, but reduced average molecular mass with a broader range of sizes present, in tissues or fluids when inflammatory or tissue remodeling processes occur. In parallel studies, exogenous hyaluronan fragments of low molecular mass (generally, less than about 200 kDa) have been shown to affect cell behavior through binding to receptor proteins such as CD44 and RHAMM (gene name HMMR), and to signal either directly or indirectly through Toll-like receptors. These data suggest that receptor sensitivity to hyaluronan size provides a biosensor of the state of the microenvironment surrounding the cell. Sensitive methods for isolation and characterization of hyaluronan and its fragments have been developed and continue to improve. This review provides an overview of the methods and our current state of knowledge of hyaluronan content and size distribution in biological fluids and tissues.